PENGGUNAAN LAHAN PERMUKIMAN PADA WILAYAH RAWAN TSUNAMI DI PERKOTAAN PACITAN JAWA TIMUR TAHUN 2022 - Fadhila Firda Azzahra; Chatarina Muryani; Setya Nugraha (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
High population growth resulted in increasingly massive development of settlements even in disaster-prone areas. Indonesia's challenge in building settlements is that most of Indonesia's population lives in disaster-prone areas. Disaster risk reduction, particularly for tsunamis, is important by controlling settlements in tsunami-prone areas. Settlement control is carried out by identifying settlements. The research aims to identify the density of residential land use blocks in tsunami-prone areas in Urban Pacitan. The research method was carried out by spatial analysis by overlaying density maps of residential land use blocks and tsunami hazard maps. For the formulation of tsunami settlement mitigation directives through regulations and existing conditions of the area. Mapping the density of residential land use blocks is obtained through the interpretation of Quickbird Imagery, then calculating the density of settlement blocks. The results of the study show that Urban Pacitan is dominated by low density residential blocks with an area of 989.7 Ha (81%). Each tsunami hazard in Urban Pacitan has three different density classifications of settlement blocks. There are 75% of the area in Urban Pacitan that is safe for settlements and 3% for conditional settlements, with special mitigation given to minimize losses due to the tsunami.